2012
DOI: 10.1097/sla.0b013e31824b31ad
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Outcome After Laparoscopic Anterior Partial Versus Nissen Fundoplication

Abstract: Mini-AbstractAnalysis of original data of 5-year outcomes from 461 patients enrolled in 4 randomized trials demonstrates that laparoscopic anterior 180˚ partial fundoplication is an effective treatment for gastroesophageal reflux, but with less side effects compared with Nissen fundoplication, although reflux control following anterior 90˚ partial fundoplication appears less effective than after Nissen fundoplication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 28 publications
3
40
0
Order By: Relevance
“…However, reinterventions for dysphagia, recurrent reflux or herniation are probably inevitable and still needed in approximately 10 per cent of patients. As to what type of fundoplication is preferred, a recent meta‐analysis supports the use of a partial fundoplication given the lower rate of dysphagia and other side‐effects3. The present study is in line with this.…”
supporting
confidence: 87%
“…However, reinterventions for dysphagia, recurrent reflux or herniation are probably inevitable and still needed in approximately 10 per cent of patients. As to what type of fundoplication is preferred, a recent meta‐analysis supports the use of a partial fundoplication given the lower rate of dysphagia and other side‐effects3. The present study is in line with this.…”
supporting
confidence: 87%
“…This is in contrast with findings of RCTs that report that 90º LAF and 120º LAF are associated with inferior reflux control in both the short [43][44][45] and the long-term. 9,46 The two main differences between 90º LAF and 120º LAF versus 180º LAF are the reduced circumference of the wrap and the lack of fixation of the wrap to the right hiatal pillar. Fixation to the right hiatal pillar is probably the main factor that accounts for differences in the risk of recurrent reflux between various anterior fundoplications and probably accounts for the good results following 180º LAF demonstrated by this meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…7 Earlier this year the long-term results of randomized trials demonstrated that 180˚ LAF offers similar reflux control compared to LNF, whereas reflux control after 90˚ LAF is less effective than after LNF. 9 A systematic review that directly compared posterior 270˚ fundoplication to LNF concluded that it reduces dysphagia and gas-related symptoms compared LNF, with similar reflux control up to 5 years. 4 A similar meta-analysis comparing outcome after 180˚ LAF and LNF has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial results were promising, with good acid control and obvious reduction in dysphagia and bloating. Unfortunately, longterm results (5 years or more) found the 90°wrap to be less effective than a 360°fundoplication, and the procedure is now rarely performed in our centers for the treatment of severe gastro-esophageal reflux disease [15,16].…”
mentioning
confidence: 99%